Modifikasi Struktur Rumah Sakit Umum Hermina Lampung dengan Metode Sistem Rangka Bresing Eksentris (SRBE) untuk Bangunan Tahan Gempa - Sarifuddin, Lukman; Isneini, Mohd; Sebayang, Surya (Universitas Lampung, 2021)
Eccentrically Braced Frame System (EBFs) is a diagonal brace system which at least one end of each supporting element supports the beam at a certain distance from the location of the beam-column joint, or from another diagonal end by a distance called a link or eccentricity. . This study aims to determine how to plan a steel structure building using the Eccentrically Braced Frame System (EBFs) method and to find out how the joint planning method for the steel structure.Hermina Lampung General Hospital is a building consisting of eight floors built using reinforced concrete construction which will be re-planned using the Eccentrically Braced Frame System (EBFs). The standard provisions in the calculations used in this study refer to SNI 1729 (2020) about cerning the Procedure for Planning Building Steel Structures.Based on the results of the research that has been done, it can be concluded that in calculating the steel frame structure using Eccentrically Braced Frame System (EBFs) can be planned based on SNI 1729 (2020) or AISC 360 (2016), but to calculate the link and brace components refer to SNI 7860 (2020) or AISC 341 (2016). Meanwhile, connection planning can be carried out based on SNI 1729 (2020) and SNI 7860 (2020) by using two methods, namely load and resistance factor design (LRFD) and allowable strength design (ASD).